2016
DOI: 10.5194/acp-16-8695-2016
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of the boreal summer tropical UTLS in observations and CCMVal-2 simulations

Abstract: Abstract. During boreal summer the upper troposphere/lower stratosphere (UTLS) in the Northern Hemisphere shows a distinct maximum in water vapour (H2O) mixing ratios and a coincident minimum in ozone (O3) mixing ratios, both confined within the Asian monsoon anticyclone (AMA). This well-known feature has been related to transport processes emerging above the convective systems during the Asian summer monsoon (ASM), further modified by the dynamics of the AMA. We compare the ability of chemistry–climate models… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 63 publications
3
14
0
Order By: Relevance
“…These results are consistent with those of Park et al [] and Park et al [], who found the maxima in MLS H 2 O and CO, respectively, during the 2005 ASM season to be nearly coincident with the region of deep convection at 215 hPa but centered within the anticyclone and distant from the deepest convection at 100 hPa. A similar shift to the northwest between the H 2 O maximum at 360 K and that at 370 and 380 K has also been seen in a multiyear July–August climatology based on Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) data [ Kunze et al , ]. Although the stratospheric tracers are primarily discussed in section 4.5.3, we note here that MIPAS ozone also showed this difference [ Kunze et al , ], as do the distributions of the MLS stratospheric tracers (Figures and S5–S7), with the westward shift in the location of the minima between 350 and 370 K especially evident in HNO 3 .…”
Section: Climatological Seasonal Evolution Of Utls Composition In Thesupporting
confidence: 80%
See 3 more Smart Citations
“…These results are consistent with those of Park et al [] and Park et al [], who found the maxima in MLS H 2 O and CO, respectively, during the 2005 ASM season to be nearly coincident with the region of deep convection at 215 hPa but centered within the anticyclone and distant from the deepest convection at 100 hPa. A similar shift to the northwest between the H 2 O maximum at 360 K and that at 370 and 380 K has also been seen in a multiyear July–August climatology based on Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) data [ Kunze et al , ]. Although the stratospheric tracers are primarily discussed in section 4.5.3, we note here that MIPAS ozone also showed this difference [ Kunze et al , ], as do the distributions of the MLS stratospheric tracers (Figures and S5–S7), with the westward shift in the location of the minima between 350 and 370 K especially evident in HNO 3 .…”
Section: Climatological Seasonal Evolution Of Utls Composition In Thesupporting
confidence: 80%
“…A similar shift to the northwest between the H 2 O maximum at 360 K and that at 370 and 380 K has also been seen in a multiyear July–August climatology based on Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) data [ Kunze et al , ]. Although the stratospheric tracers are primarily discussed in section 4.5.3, we note here that MIPAS ozone also showed this difference [ Kunze et al , ], as do the distributions of the MLS stratospheric tracers (Figures and S5–S7), with the westward shift in the location of the minima between 350 and 370 K especially evident in HNO 3 .…”
Section: Climatological Seasonal Evolution Of Utls Composition In Thesupporting
confidence: 80%
See 2 more Smart Citations
“…1) The second method is a multiple linear regression (MLR) technique. The MLR code is the same as that used and described in SPARC (2010), with a similar method also used in Bodeker et al (1998) and Kunze et al (2016). In this case, the time evolution of a variable, y(t), can be defined as:…”
Section: The Analysis Methods 25mentioning
confidence: 99%